Conceptualising cultural ecosystem services: A novel framework for research and critical engagement - Fish, Robert; Church, Andrew; Winter, Michael (Ecosystem services, 2016)
The construction of culture as a class of ecosystem service presents a significant test of the holistic ambitions of an ecosystems approach to decision making. In this paper we explore the theoretical challenges arising from efforts to understand ecosystems as objects of cultural concern and consider the operational complexities associated with understanding how, and with what consequences, knowledge about cultural ecosystem services are created, communicated and accounted for in real world decision making. We specifically forward and develop a conceptual framework for understanding cultural ecosystem services and related benefits in terms of the environmental spaces and cultural practices that arise from interactions between humans and ecosystems. The types of knowledge, and approaches to knowledge production, presumed by this relational, non-linear and place-based perspective on cultural ecosystem services are discussed and reviewed. The framework not only helps navigate more fully the challenge of operationalising ‘cultural ecosystem services’ but points to a more relational understanding of the ecosystem services framework as a whole. Extending and refining understanding through more ambitious engagements in interdisciplinarity remains important. •Understanding and accounting for cultural ecosystem services requires a relational approach.•A novel framework for developing this relational approach is described and illustrated.•Framework advances new analytical and empirical categories for research and practice.•Application of the framework requires pluralistic methodologies and strong interdisciplinarity.